Pengaruh Ekstrak Etanol 96% Bawang Dayak (Eleutherine Palmifolia (L.) Merr.) Terhadap Pertumbuhan Methicillin Resistant Staphylococcus Aureus (MRSA) - Feriandri Utomo; Laura Nurul Alfiola (Jurnal Kesehatan Islam : Islamic Health Journal, 2022)
The number of Methicillin Resistant Staphylococcus aureus (MRSA) continues to increase.The antibiotics used to treat MRSA infections is vancomycin, but the number of Staphylococcius aureus bacteria that are resistant to vancomycin has also increased. Dayak onion as a medicinal plant which has been used for a long time, has antibacterial compounds namely flavonoids, tannins, terpenoids, and quinones.The purpose of this study was to analyze the effect of 96% ethanol extract of Dayak onion with concentrations of 12.5%, 25%, 50% on the growth of MRSA compared to vancomycin, and to determine the phytochemical content of MRSA antibacterial compounds in Dayak onions.The study design used a post test only with control group by giving 0.9% NaCl to the negative control group. MRSA growth in this study was assessed from the size of the inhibition zone by the Kirby-Bauer method. Data analysis using One-Way ANOVA , then continued post hoc test. The results of this study indicated that Dayak Onion had weak anti-bacterial activity against MRSA, so it is not effective as an anti-bacterial MRSA because an average inhibition zone of <15mm is formed in all concentration groups (10.88mm at 12,5 % concentration, 12.35mm at 25 % concentration, and 14.35mm at 50% concentration). The average diameter of the inhibition zone in the treatment group of Dayak onion extract with 12,5 % concentration was significantly lower (p value <0.05) than the average diameter of the inhibition zone in the treatment group with 50 % concentration of the Dayak onion extract. The average diameter of the inhibitory zone in the treatment group of all concentrations of Dayak onion extract was significantly lower (p value <0.05) than the average diameter of the inhibition zone in the Vancomycin treatment group. The average inhibition zone formed in the vancomycin treatment group was 22.29 mm, so it was still effective as an anti-bacterial MRSA. This study also found the presence of flavonoid compounds, terpenoids, tannins, and quinones in Dayak onions. Therefore, it can be concluded that the 96% ethanol extract of Dayak onion which contains phytochemical anti-bacterial compounds has weak activity in inhibiting the growth of MRSA, so it is not effective as anti-bacterial for MRSA.